Mechanical characterization of composites polyester moulding reinforced waste metal lathes with standard ASTM D 638-lll modification - Idris, Iswandi; Aditya Sari, Ruri; ., Hendriko; Novia Syamsir, Hendri (International Journal of Engineering and Technology, 2018)
Scope and Objectives of this research are: To improve the mechanical characteristics of polyester composite fabricated waste metal lathe and Styrofoam through tensile test, compression test, impact test, obtain a new note for developing new composite materials by use waste metal lathe and plastic waste Styrofoam in order not to waste. from the test results obtained tensile strength 0.66 kg f/ mm2, greatest moment 5,490 kg f.m, greatest stress 1.93 kg f/ mm2, strain 0.17093 m/m and bending angle 167.64. The breakpoints of the composite specimen in which the waste lathe located is at 0.65, the elastic behaviour seen from the number 0 to the 1.06 proportional limit, then at the voltage level 1.1 of the plastic behaviour and the 1.633 level has undergone plastic deformation until the breakpoints. The charphy impact implies 110 (J / mm 2). From the experimental results showed that the composite fabric waste has good mechanical properties.